GIANT CELL TUMOR OF THE RIBS: A CASE REPORT - I Putu Gede Pradnyadewa Pradana; Mouli Edward (Journal Orthopaedi and Traumatology Surabaya, 2021)
Background: Giant Cell Tumor (GCT) is a benign tumor but can be malignant and spread to other organs. Common site of GCT develops in long bone, especially in the knee. A lesion that develops in flat bone is considered rare. This case report aims to recognize GCT of bone and its predilection and help improve diagnostics and manage this case to provide better results.Case Report: A seven-year-old female came with complaints of lump and intermittent pain in left-back. The lump is gradually getting more prominent. The pain is localized in the back mid-area, worsen with any touch around the area. On examination, there is deformity and mass on the posterolateral side at the 9th rib level around 3 cm in diameter. There was tenderness on palpation and limited range of motion (ROM). The cytological and radiological finding suggests GCT of bone. The patient had resection surgery of the lesion. The histopathologic results on the operative specimens confirmed the diagnosis of GCT.Discussion: An unusual location of GCT lesions needs to be a concern because they can be underdiagnosed not to receive optimal therapy. Inadequate therapy can increase the incidence of recurrence and malignancy changes. In this case, the patient had resection surgery. Postoperatively, the patient is in good condition with no sign of local recurrence.Conclusion: GCT should be included in the differential diagnosis of rib-originated tumors.  Tumor lesions in unusual places other than long bones and occurs on the immature patient should be particular concern and confirmed diagnosis.